Ergonomical Evaluation of a Hand Operated Paddy Winnower by Women Workers - Singh, S P; Gite, L P (Journal of Agricultural Engineering, 2007)
A hand operated paddy winnower was developed by Central Rice Research Institute, Cuttack. The winnower was ergonomically evaluated using 12 subjects. Two women workers are required for the operation of this winnower, one for cranking the blower and other for feeding the threshed material and collection of grain. The mean heart rate of the women workers and their output were measured to evaluate the winnower. The mean heart rate of women workers during operation was found to be 112 beats/min. The energy expenditure rate in operation of the equipment was 10.7 kJ/min. The average output was found to be 242 kg grain/h and winnowing efficiency was found to be 88.36%. The equipment developed was found to be suitable for operation by women workers as the heart rate, work pulse value and energy expenditure rate are within the acceptable limits.